SOCIAL EMBEDDEDNES AND ITS NETWORK IN COFFEE SHOP BUSINESS IN JOMBANG REGENCY - Permatasari, Bella Dwi; Trinugraha, Yosafat Hermawan; Parahita, Bagas Narendra (Program Studi Sosiologi Universitas Malikussaleh, 2024)
This research aims to determine the social embeddedness and networks that occur in a coffee shop business in Jombang Regency. This research uses a qualitative descriptive method with case studies as the approach. Social embeddedness in the form of relational embeddedness and structural embeddedness that exist in the coffee shop business shows that there is a social relationship that occurs between consumers and the coffee shop which arises from their trust in the coffee shop. Furthermore, structural embeddedness shows collaboration built by the coffee shop with other parties with the aim of building relationships and business continuity. Apart from that, the sustainability of the coffee shop business cannot be separated from the influence of existing social networks, namely social networks between coffee shop owners, social networks between coffee shop owners and employees, social networks between fellow coffee shop employees, and social networks between employees and consumers coffee shop.